(Essential Oil from the Leaves and Steams of The red Ginger Plant A Rich Source Of Linally Acetate) - Salya Sait; Enny Hawani Loebis (Balai Besar Industri Agro, 1989)
The chemical constituents of an essential oil obtained from the leaves and stems of the plant Zingiber officinale Roscoe of a red type, have been studied using gas -liquid chromatography. The oil contains linalyl acetate (37.9%) as the major component. Some other abundant constituents were also identified which are geranial (9.35%), neryl acetate (6.23%), terpenyl acetate (5.66%), and one which is still unidentified (6.78%). The high content of linalyl acetate showed that the oil, which is comparable to that of bergamot oil, be a valuable commodity and affirms that another type of essential oil has been recognized.